Effects of differential contacts with the criminal legal system on mental health outcomes of adolescents and young adults: A fixed-effects model - Raquel V. Oliveira; Elizabeth Culatta (PLoS ONE, 2026)
Research has indicated that contacts with the criminal legal system may have detrimental consequences for health and well-being. There is, however, a lack of research exploring how different types of interactions with the criminal legal system may impact mental health. Our study aims to address the gap in the literature by exploring progressively more severe forms of criminal legal contact on a variety of mental health symptoms using the Pathways to Desistance Study (PDS), a longitudinal sample of youth (2000–2010) who have a high level of contact with the criminal legal system (N = 1,322). Using fixed-effects modeling, we examine how specific types of contact with the criminal legal system (e.g., arrests, court appearances, institutionalization) are associated with mental health outcomes including symptoms of anxiety, depression, hostility, and psychoticism. We found that arrests and institutionalization have significant cross-sectional associations with multiple mental health symptoms, while appearing in court was associated with more long-term increases in reported mental health symptoms. We also observed that substance use, criminal involvement, and use of mental health medication were consistently associated with mental health outcomes across 10 waves of data. Thus, our paper evidences that even less severe contacts with the criminal legal system appear to be stressors that can have both short-term and long-term effects on mental health symptoms in youths and young adults.